1978
DOI: 10.1139/g78-043
|View full text |Cite
|
Sign up to set email alerts
|

NUCLEOLAR ORGANIZER REGIONS IN THE RABBIT (ORYCTOLAGUS CUNICULUS) AS SHOWN BY SILVER STAINING

Abstract: Nucleolar organizer regions (NOR's) were demonstrated in metaphase chromosomes of the domestic rabbit. Oryctolagus cuniculus (L.) (New Zealand white strain) using silver staining. Sequential quinacrine banding and a modification of the Ag-AS silver precipitation technique with duplicate photography allowed identification of silver staining NOR's on the short arms of chromosomes 13, 16, and 20, as well as the telomeric region of the long arms of number 21 in some cells. Chromosomes 13, 16 and 20 all have subter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…For example, in the human these genes are found on five pairs of autosomes, in the mouse on eight pairs, in cattle also on five pairs, and in pig and rat on three chromosome pairs. Our data are in agreement with previous studies in the rabbit in which nucleolar organizer regions were identified at the same locations by sequential Qbanding and silver staining (Martin-DeLeon et al, 1978). Furthermore, the present data confirm the localization that was achieved by hybridization of RNA probes in radioactive in situ hybridization experiments (Martin-DeLeon, 1980).…”
Section: Resultssupporting
confidence: 93%
“…For example, in the human these genes are found on five pairs of autosomes, in the mouse on eight pairs, in cattle also on five pairs, and in pig and rat on three chromosome pairs. Our data are in agreement with previous studies in the rabbit in which nucleolar organizer regions were identified at the same locations by sequential Qbanding and silver staining (Martin-DeLeon et al, 1978). Furthermore, the present data confirm the localization that was achieved by hybridization of RNA probes in radioactive in situ hybridization experiments (Martin-DeLeon, 1980).…”
Section: Resultssupporting
confidence: 93%
“…The only possible comparison of Ag-NOR position is with Oryctolagus cuniculus (Martin-DeLeon 1980 ;Martin-DeLeon et al 1978 ;Monteagudo and Arruga 1991); this species shows the occurence of Ag-NORs in three pairs of chromosomes which might correspond to those of L. starcki, but also in a pair of small acrocentrics which do not find any homologue in our data.…”
Section: Resultsmentioning
confidence: 53%
“…The karyotype chromosomes are divided into three morphological groups: metacentric (34 autosomes), acrocentric (8 autosomes) and submetacentric (sex chromosomes) (ROBINSON et al 2002). The rabbit karyotype pattern of G, Q, R, C and NOR banded chromosomes has been determined (HAGELTRON & GUSTAVSSON 1979;POULSEN et al 1988;MARTIN-DELEON et al 1978;OEWITOÑSKI et al 1982;YERLE et al 1987;RqNNE 1995;KUCHTA et al 2009) and banding patterns have also been established. The rabbit karyotype has been used for comparisons with the human karyotype (DUTRILLAUX 1980).…”
mentioning
confidence: 99%